Soil cover with accelerated erosion processes (Revista Sistemas de Producción Agroecológicos, 2015)
The aim of the study was to evaluate the introduction and persistence in soil mulched with accelerated erosion in Puerto Gaitan, Meta, where various species and soil management practices was evaluated. Fertilization of the experimental plots was performed with a base saturation of 35-50% and phosphorus levels between 5 and 10 ppm. Corrective used were lime dolomite, phosphate rock, fertilizer Peace River and magnesium oxide. The strategic activities that were raised included: assessment of herbaceous (grasses and legumes) alone or in combination with trees and bushes; assessment practices, tillage systems and technology transfer. In soil was assessed for three years dynamics chemical characteristics: pH, organic matter, P, Ca, Mg, K, S, Al, Fe, Cu, Mn, Zn and B at various depths (0-10, 0-20 cm or according to the dominant horizons), during the time of maximum and minimum precipitation. Emergence (%); height (cm); coverage (%); pest and disease attack; distribution and root development of species with outstanding production and quality of dry green biomass and litter was evaluated in plant species. At the end of the establishment B. dictyoneura, B. decumbens, B. humidicola and D. ovalifolium showed the highest soil cover (P
Keywords: vegetation; grasses; biomass; recovery